Analysis of Qawa’id Fiqhiyyah in the Utilization of Zakat as a Solution to Illegal Online Loans - Efendi, Nur; Bisri, Hasan; Yunus, Ayi; Luminaries, Rayan Asa (Al-Muamalat: Jurnal Ekonomi Syariah, 2025)
The phenomenon of online loans has become a pressing societal issue, affecting many individuals struggling with debt repayment, contributing to rising suicide rates. Zakat, as an Islamic social finance instrument, should help mitigate these negative impacts. This article examines the utilization of zakat funds as a solution to the online loan crisis from the perspective of Qawa’id Fiqhiyyah (Islamic legal maxims). Using a normative juridical approach with descriptive analysis, this study explores the application of Qawa’id Fiqhiyyah in utilizing zakat funds to address online loan issues. The findings reveal that zakat can address online loan problems, aligning with the maxim that “harm must be eliminated.” Borrowers often experience harm, such as threats, intimidation, and data breaches when they cannot repay debts. Zakat offers assistance to victims, helping them avoid actions violating Islamic principles, in line with the maxim “hardship brings ease.” However, borrowers must meet the gharim criteria, especially if the loans were used to purchase prohibited items under Islamic law. This study provides a novel perspective on zakat by employing the Qawa’id Fiqhiyyah approach to tackle the issue of online loans in Indonesia.